1982
DOI: 10.1007/978-1-349-16681-7
|View full text |Cite
|
Sign up to set email alerts
|

Monopoly Capitalism

Abstract: Debates between economists are not just technical arguments amongst practitioners but often reflect philosophical and ideological positions which are not always made explicit. Discontent grew with the prevailing economic orthodoxy as the long period of economic expansion in the advanced capitalist economies came to an end in the 1970s; disenchantment was expressed in open discussion about the 'crisis' in economics and in the rise of various kinds of radical economic theory, often using the general title of 'po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 0 publications
4
82
0
1
Order By: Relevance
“…managers and/or a controlling subset of the shareholders and managers, see e.g. Galbraith [1967] and Cowling [1982]. Further, building upon Williamson [19641 it may be suggested that those in control of corporations save and consume within the corporations.…”
Section: Definitions Of Variablesmentioning
confidence: 99%
“…managers and/or a controlling subset of the shareholders and managers, see e.g. Galbraith [1967] and Cowling [1982]. Further, building upon Williamson [19641 it may be suggested that those in control of corporations save and consume within the corporations.…”
Section: Definitions Of Variablesmentioning
confidence: 99%
“…(This model new provides the micro-economic foundation of the post-Keynesian theory of growth and distribution. See, for example, Asimakopolous, 1980;Cowling, 1982;Dixon, 1983;Sawyer, 1982;and Sylos-Labini, 1979a. ) Firms are assumed to determine their prices by applying a mark-up to their normalized unit variable costs.…”
Section: T H E Cobb-douglas R E L a T I O N S H I P A N D Kaleckimentioning
confidence: 96%
“…This may be shown to be a special case of a more general theory of profit maximization under oligopolistic conditions. Following Cowling (1982), the firm is assumed to maximize the profit function It follows that a condition for profit maximization is where -q is the price elasticity of demand and 8 equals (dY/dYi). The share of profits for industry as a whole is given by (where C S: is the Herfindahl measure of industrial concentration).…”
Section: T H E Cobb-douglas R E L a T I O N S H I P A N D Kaleckimentioning
confidence: 99%
“…Among the latter, see Moore (1988, p. 21 3) for instance, and among the former see Cowling (1982) and several other interpreters of Kalecki. profit maximizing rule, based on a pricing decision where the mark-up is set so as to equalize marginal revenue to marginal cost.5 To preserve the theoretical autonomy of normal cost pricing, it then becomes imperative to deny that variable costs are constant, and that full cost pricing, normal cost pricing or target return pricing can be subsumed to mark-up pricing on variable costs. In this manner, overhead or fixed costs enter the pricing decision, something that is incompatible with marginal pricing.…”
Section: Pricing In Post-keynesimz Moclels 59mentioning
confidence: 97%